Michael Davitt’s Wartime Visit to South Africa (March-May 1900) and its Consequences - McCracken, Donal P (Scientia Militaria - South African Journal of Military Studies, 2019)
In view of renewed interest in the radical Irish nationalist leader and land reform agitator Michael Davitt and his ideas, this article reconsiders his much publicised fact-finding visit to the war-torn Boer republics in South Africa and its context. Davitt resigned as an Irish nationalist member of parliament (MP) from the British House of Commons over the Anglo-Boer War, rather than any Irish issue. He was in South Africa from late March to early May 1900, where he met the leaders of the republics and senior generals. On his return to Ireland, Davitt wrote a 600-page partisan book on the Anglo-Boer War. The South African experience remained special to him. After his return to Europe, Davitt became closely associated with the Kruger-exile coterie, drifting away from mainline Irish nationalism. This article traces Davitt’s visit and discusses the effect it had on him, on Irish nationalism and on the Boer republics he visited.